Optimization of Suction Channel System on Vacuum-Type Soybean Seed Metering System Powered by Hand Tractor - Adhiasta Faris Setiabudi; Wawan Hermawan; Radite Praeko Agus Setiawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
A vacuum-type soybean seeder powered by hand tractor for Indonesia’s local soybean has been developed to overcome soybean low productivity. The developed machine still has a weakness in the context of the suction channel system. This research was conducted to optimize the suction channel system efficiency, suction performance for bigger type of seed variety, and suction effect uniformity on all metering device. The research step consisted of seed characteristic measurement for two Indonesia’s common local soybean seed variety (Anjasmoro and Grobogan), suction channel system modification and analysis, and validation based on computational fluid dynamic (CFD). The result in this research are proposed 3-types of optimized model with final selection of 1-type of model, namely Branch model. The values produced by the optimized model compared to existing model respectively 3.393 kPa (CV 0.10%) and 3.112 kPa (CV 1.54%) for negative pressure, 14.39 m/s (CV 4.11%) and 9.08 m/s (3.44%) for suction velocity, as well as 117.342 Pa and 118.147 Pa for total pressure-loss. The required value for Anjasmoro and Grobogan seed variety respectively 3.094 kPa and 3.358 kPa for negative pressure pressure, as well as 10.22 m/s and 10.03 m/s for suction velocity. Hence, the selected optimized model is more efficient, uniform, and can accommodate required negative pressure pressure and suction velocity for both Anjasmoro and Grobogan, while the existing model can only accommodate Anjasmoro. Keywords: CFD, Metering device, Optimization, Pneumatic, Soybean.